Adaptive super-twisting fractional-order nonsingular terminal sliding mode control of cable-driven manipulators. (March 2019) - Wang, Yaoyao; Chen, Jiawang; Yan, Fei; Zhu, Kangwu; Chen, Bai
Abstract: This paper proposes a novel adaptive super-twisting fractional-order nonsingular terminal sliding mode (AST–FONTSM) control scheme using time delay estimation (TDE) for the cable-driven manipulators. The designed control scheme utilizes TDE to obtain the estimation of system dynamics, and therefore no system dynamic model information will be required. Afterwards, AST and FONTSM schemes are applied to ensure good control performance in both reaching and sliding mode phases. Due to the adoption of AST scheme, good robustness and high control precision are obtained in the reaching phase, while the boundary information of the lumped uncertainties will be no longer required. Thanks to the utilization of FONTSM error dynamics, fast convergence and accurate tracking and strong robustness can be simultaneously ensured in the sliding mode phase. Corresponding comparative simulation and experimental results demonstrate the effectiveness and superiorities of our proposed method over the existing control methods. Highlights: Propose a novel AST scheme using a newly designed adaptive algorithm. Propose a novel AST–FONTSM control scheme with TDE technique. Perform the stability analysis considering the AST and FONTSM error dynamics. Demonstrate the superiorities of proposed method through both simulations and experiments.